Roles of Factor XII in Innate Immunity - Renné, Thomas; Stavrou, Evi X. (Frontiers in Immunology, 2019)
Factor XII (FXII) is the zymogen of serine protease, factor XIIa (FXIIa). FXIIa enzymatic activities have been extensively studied and FXIIa inhibition is emerging as a promising target to treat or prevent thrombosis without creating a hemostatic defect. FXII and plasma prekallikrein reciprocally activate each other and result in liberation of bradykinin. Due to its unique structure among coagulation factors, FXII exerts mitogenic activity in endothelial and smooth muscle cells, indicating that zymogen FXII has activities independent of its protease function. A growing body of evidence has revealed that both FXII and FXIIa upregulate neutrophil functions, contribute to macrophage polarization and induce T-cell differentiation. In vivo, these signaling activities contribute to host defense against pathogens, mediate the development of neuroinflammation, influence wound repair and may facilitate cancer maintenance and progression. Here, we review the roles of FXII in innate immunity as they relate to non-sterile and sterile immune responses.